Phonemic Hermeneutics of Eschatological Intonation in Sūrat Al-Qiyāmah Recitation - Ahid Ilham Zulfiqar; Diyan Rifky Ramdhani; Lina Marlina (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to analyze the eschatological pitch movements in Misyārī Rāsyid al-‘Afāsī’s recitation of Sūrat Al-Qiyāmah and to interpret their semantic-pragmatic meanings through al-‘Ani’s pitch-level framework. Using a descriptive qualitative phonemic approach, this study examines twenty-nine eschatological verses selected from Sūrat Al-Qiyāmah based on classical exegetical boundaries. The primary data were obtained from al-‘Afāsī’s murattal audio recitation, while the semantic baseline was established through six authoritative tafsir works. Data were collected through repeated listening, note-taking, pitch-pattern classification, and digital pitch-contour visualization. The analysis applied Nasution’s five-category pitch typology and al-‘Ani’s four-level pitch notation. The findings show that falling pitch dominates the corpus, appearing in 41.4% of the verses, followed by falling-rising pitch at 31.0%, rising-falling pitch at 17.2%, rising pitch at 6.9%, and flat pitch at 3.4%. The application of al-‘Ani’s framework indicates that 37.9% of the data show semantic-pragmatic congruence, 13.8% show incongruence, and 48.3% remain undetermined due to the complexity of Qur’anic illocutionary functions. The most significant finding appears in Q. 75:40, where an interrogative construction is recited with falling pitch to encode absolute theological affirmation. This study proposes the concept of phonemic hermeneutics, namely the interpretive function of pitch in Qur’anic recitation. The findings contribute to Arabic prosody, Qur’anic phonology, and taḥsīn pedagogy by showing that intonation is not merely vocal ornamentation, but a semantic-pragmatic device that supports meaning-conscious recitation.